An Evaluation On The Viability On The Post-Harvested Stored Wheat Grains - DR. SHIJU MATHEW (International Journal of Pharma and Bio Sciences, 2010)
The seed viability of stored wheat grains was checked by sprouting test. The germination studies shown that viability of the stored wheat grain reduces on storage. The study has shown that the U.P. 262 has much more sprouting capability as compared to H.D. 1982. The sprouting capacity of both the varieties analyzed showed a decrease to about 70% after three years of storage. After 3 years it takes from days to weeks and in some cases even months for sprouting to be complete. The seed viability approaches was utilized to understand the wheat grain quality under post harvest storage. Thus concrete steps should be taken to improve the storage conditions in the government godowns which is the single largest granary of India. It was observed that a holistic ecological view is needed when considering management approaches to long-term-storage of wheat grains for the maintenance of quality. Methodologies should be examined to develop a new and better method for preservation of stored wheat grains with minimal loss of nutrient content. The germination capacity of the stored wheat grain reduces with time. The research paper helps to determine the sprouting capacity of stored wheat grains for agricultural purposes. The grain losses found in quantity and quality; can be in the form of depletion in seed viability, hardness, colour, size and shape, grain weight under post harvest storages.